ELEMEN DAN MAKNA GERAK TARI DARA NGINDANG DI SANGGAR SENI TERUNA BEBADOSAN DESA LENEK KECAMATAN LENEK, LOMBOK TIMUR - Muhimmah, Siti Hidatullah (TAMUMATRA, 2019)
The research aims to know the elements and the meaning of Dara Ngindang Dance Motion at Lenek villageof Bebadosanart Teruna Art. The study used the theory of motion element and semiotics theory of Charles Sanders Peirce. The study used was qualitative descriptive. The result of this study shows that there are three, the supporting elements of Dara Ngindang dance, namely space, time and energy. The meaning of found in Dara Ngindang dance motion of by  using the theory is ngindang in qualisign meaning dynamic and freedom, nyumping in away. Qualisign means soft and gracefully, joltak in sinsign means jumping, mematuk in sinsign means eating, bekerap in qualisign  means standard and degrees, bekeketer in sinsign means mating, as well as motion begeroh in sinsign means menggiring (leading).